Fasciocutaneous flaps in the management of soft-tissue defects of the lower leg caused by explosive weapons - Petković Aleksandar; Trenkić Srbobran; Stevanović Goran R.; Rančić Zoran S.; Golubović Zoran; Dinić Miodrag; Krasić Dragan (Vojnosanitetski Pregled)
The use of fasciocutaneous flaps for the reconstruction of lower leg soft-tissue defects inflicted during the bombing of our country is presented in this case report. The experience with 9 patients with soft-tissue defects of the lower leg is presented with the aim of examining the possibilities of war-wound reconstruction. The results of the earlier use of fasciocutaneous flaps in the lower leg reconstruction as well as the those obtained during the reconstruction of the lower leg soft-tissue defects in war wounds was proven to be safe and reliable method of the reconstructions of severe lower leg injuries, particularly of its distal segment and the malleolus region.